INFLUENCE OF MOTIVATION, TRAINING, SKILL AND UTILIZATION OF TECHNOLOGY ON THE IMPLEMENTATION OF INFORMATION MANAGEMENT SYSTEM REGIONS ON EMPLOYEES’ PERFORMANCE WITH THE SUPERIORS’ SUPPORT AS A MODERATING VARIABLE (Empirical Study at the Regional Financi - Hidayati, Erni (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of motivation, training, skill, and the use of technology in implementing regional management information system on employees’ performance at BPKAD (Regional Financial and Assets Management Agency) of Langkat Government Regency with superiors’ support as moderating variable. The research used causal comparative method. The population was 71 BPKAD employees as the respondents. The research method was census method. The hypothesis was tested by using multiple linear regression analysis. The result of the research showed that motivation, training, skill, and the utilization of technology simultaneously had the influence in implementing regional management information system on the employees’ performance at the BPKAD of Langkat Government Regency. Partially, motivation, skill, and the utilization of technology had positive and significant influence in implementing regional management information system on the employees’ performance at the BPKAD of Langkat Government Regency, but training did not influence the employees’ performance at the BPKAD of Langkat Government Regency, Superiors’ support as moderating variable could moderate the correlation of motivation, training, skill, and the utilization of technology in implementing regional management information system with the employees’ performance at the BPKAD of Langkat Government Regency.